2000
DOI: 10.1785/0119980186
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phase Velocities from Array Measurements of Rayleigh Waves Associated with Microtremor and Results Calculated from Borehole Shear-Wave Velocity Profiles

Abstract: Shear-wave velocities (V S ) are widely used for earthquake groundmotion site characterization. V S data are now largely obtained using borehole methods. Drilling holes, however, is expensive. Nonintrusive surface methods are inexpensive for obtaining V S information, but not many comparisons with direct borehole measurements have been published. Because different assumptions are used in data interpretation of each surface method and public safety is involved in site characterization for engineering structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(11 citation statements)
references
References 21 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…For example, patterns of ground motion amplification observed during earthquakes are comparable to amplification patterns modelled from microtremor data (Horike, Zhao and Kawase 2001; Rodriguez and Midorikawa 2003; Cara et al 2008; Haghshenas 2008). Similarly shallow shear‐wave velocities determined from the analyses of microtremor data have been verified through application of downhole measurements and seismic refraction profiles (Liu et al 2000; Louie 2001; Di Giulio et al 2006).…”
Section: Introductionmentioning
confidence: 73%
“…For example, patterns of ground motion amplification observed during earthquakes are comparable to amplification patterns modelled from microtremor data (Horike, Zhao and Kawase 2001; Rodriguez and Midorikawa 2003; Cara et al 2008; Haghshenas 2008). Similarly shallow shear‐wave velocities determined from the analyses of microtremor data have been verified through application of downhole measurements and seismic refraction profiles (Liu et al 2000; Louie 2001; Di Giulio et al 2006).…”
Section: Introductionmentioning
confidence: 73%
“…In Asten et al () a blind comparison was reported between passive surface wave recordings, seismic CPT and seismic refraction at a site with about 20 m of soft soil (VS= 130−140 m/s), overlying firm glacial till (VS= 550 m/s). Liu et al () reported the case of alluvial sediments (about 100 m thick) overlying granite bedrock with shear‐wave velocity slightly higher than 1500 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…Rayleigh wave dispersion is typically considered as a good constraint on the S wave structure [Lai and Rix, 1998;Liu et al, 2000;Louie, 2001]. A systematic search of model parameters based on the ranges determined from the refraction results (Table 1) was performed to empirically examine the effects of seismic velocities and thicknesses on the measured Rayleigh wave phase velocity dispersion.…”
Section: Hammer-generated Rayleigh Wave Dispersion Analysismentioning
confidence: 99%